Analisis Peluang dan Tantangan Pengembangan Agroindustri Kelapa - Suci Wulandari (Agroindustrial Technology, University of Trunojoyo Madura, 2010)
The organization as a pool of resources, capabilities and competencies needed togenerate physical products or intangible services which create the competitive advantage. It isdeveloped by effective management of technical aspects and by learning aspects of theorganization, and also the influence of an effective networking. How these two factors work toestablish value of the organization then effect the degree of competitiveness, is influenced byhow much the assets owned by an organization. This value is categorized into tangible andintangible assets. Development of coconut-based products shows a meaningful opportunity inthis regard. On the other hand, changes in the global environment have brought changes in thebehavior of consumers and competition conditions. Review of the role, coconut commoditiesprovides a great role to the economy nationally. Indonesia is a country with the largest area ofcoconut production in the world, followed by The Fillippines and India. Exports of coconutproducts from Indonesia tended to increase. The size of the role and potential of coconut wasnot followed by the performance of the coconut industry. This is shown by the problemsassociated with value-added products, linkages, transfer the risks and benefits, the contributionfor the development of rural agro-industry, export value of products, industrial competitivenessin medium and small agro-industry in the global market and information flow. Optimizing thevalue of intangible assets in the system of agro-industry can be improved through theimplementation of Knowledge Management occurred through developing external structure,internal structure and individual competency. Application of Knowledge Management refers tothe model of two dimensions, namely the process of knowledge creation and innovation, andelements that enable or influence the activities of knowledge creation. This model isimplemented by using Knowledge Management Roadmap which consists of 10 steps in 4phases. Through the implementation of Knowledge Management, coconut agroindustry isexpected to become the business units that have optimal value capable of performingcompetitiveness. Finally, it will satisfy the consumers through on time delivery product, createthe customer loyalty which in turn increase the sales growth and gain the result in financialaspects in earning growth